2006
DOI: 10.1080/00016350500483152
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of the bactericidal activity ofHarungana madagascariensisLam. ex Poir. (Hypericaceae) leaf extract against oral bacteria using poly (D, L-lactide-co-glycolide) nanoparticles:in vitrostudy

Abstract: Harungana madagascariensis Lam. ex Poir. (Hypericaceae) is known to have biological properties with mainly antibacterial, antifungal, and antiviral effects. The objective of this study was to investigate the in vitro bactericidal activity of the ethyl acetate H. madagascariensis leaf extract (HLE) on the main oral bacterial strains largely implicated in dental caries and gingivitis infections, and the possibility of potentialization of HLE antibacterial effects using the poly (D,L-lactide-co-glycolide) nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…[1] The orange red resinous sap from the bark has been associated with wound healing properties. [2] In one instance, leaf aqueous extract of the plant was reported to show antimicrobial activity [3] while a diminution of oral bacteria was also reported by Moulari et al [4] in an in vitro study. However, in a separate study by Moulari et al, [5] a flavanone, astilbin was isolated as the antibacterial principle.…”
Section: Introductionmentioning
confidence: 74%
“…[1] The orange red resinous sap from the bark has been associated with wound healing properties. [2] In one instance, leaf aqueous extract of the plant was reported to show antimicrobial activity [3] while a diminution of oral bacteria was also reported by Moulari et al [4] in an in vitro study. However, in a separate study by Moulari et al, [5] a flavanone, astilbin was isolated as the antibacterial principle.…”
Section: Introductionmentioning
confidence: 74%
“…This is also confirmed in this study. The study therefore showed that antimicrobial compounds also reside in the stem bark like the leaves (Okoli et al, 2002;Moulari et al, 2006aMoulari et al, , 2006b) with the highest activities found in the acetone, dichloromethane, chloroform and ethyl acetate extracts. H. madagascariensis has been used traditionally for the treatment of various respiratory, gastro-intestinal, sexual transmission and parasitic diseases by the people of east and west Africa for a long time (Kamanzi Atindehou et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Kouam et al (2007) have isolated a prenylated 1, 4-anthraquinone from the hexane extract of the stem-bark of H. madagascariensis and have shown it to possess G-glucosidase inhibition and antioxidant activities. Most of the investigations on the pharmacological efficacies of H. madagascariensis are based on the leaves (Madubunyi et al, 1995;Kamanzi Atindehou et al, 2002;Okoli et al, 2002;Moulari et al, 2006aMoulari et al, , 2006bKouam et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, researchers reported that several essential oils from plants had antibacterial activity against oral bacteria (1). The oolong tea polyphenols possess a strong antiglucosyltransferase activity and inhibit experimental dental caries in species pathogen-free rats infected with mutans streptococci (12,13). Cacao beans, which form the main constituent of chocolate, contain some polyphenols which exhibit antiglucosyl transferase activity (14).…”
Section: Discussionmentioning
confidence: 99%